Search for top squark pair production in compressed-mass-spectrum scenarios in proton-proton collisions at $\sqrt{s}$ = 8 TeV using the $α_T$ variable - CMS collaboration (2296 authors) (2017)
An inclusive search is performed for supersymmetry in final states containing jets and an apparent imbalance in transverse momentum, p→Tmiss , due to the production of unobserved weakly interacting particles in pp collisions at a centre-of-mass energy of 8 TeV. The data, recorded with the CMS detector at the CERN LHC, correspond to an integrated luminosity of 18.5 fb −1 . The dimensionless kinematic variable αT is used to discriminate between events with genuine p→Tmiss associated with unobserved particles and spurious values of p→Tmiss arising from jet energy mismeasurements. No excess of event yields above the expected standard model backgrounds is observed. The results are interpreted in terms of constraints on the parameter space of several simplified models of supersymmetry that assume the pair production of top squarks. The search provides sensitivity to a broad range of top squark ( t˜ ) decay modes, including the two-body decay t˜→cχ˜10 , where c is a charm quark and χ˜10 is the lightest neutralino, as well as the four-body decay t˜→bff¯′χ˜10 , where b is a bottom quark and f and f¯′ are fermions produced in the decay of an intermediate off-shell W boson. These modes dominate in scenarios in which the top squark and lightest neutralino are nearly degenerate in mass. For these modes, top squarks with masses as large as 260 and 225 GeV are excluded, respectively, for the two- and four-body decays.